The Role of the Humanities in Rural Community Development - Jans, Sheila (Maine Policy Review, 2015)
Maine’s rural communities are facing some serious economic and social challenges. Sheila Jans explores the crucial role that the humanities play in tackling some of these challenges. The humanities provide a powerful and nimble way to generate ideas and solve problems. Examples of humanities-based initiatives and experiences in the St. John Valley at the northernmost point of Maine, bordering Canada, provide insight into the role of the humanities as a tool for development.
Keywords: humanities; community development; Maine